2003
DOI: 10.1080/02786820300932
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Particle Deposition in an Idealized Mouth with Different Small Diameter Inlets

Abstract: The deposition of monodisperse particles (1.0-12.5 µm diameter) in an idealized mouth geometry has been studied numerically for three different inlet diameters

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 30 publications
(34 reference statements)
2
30
0
Order By: Relevance
“…This model is an average geometrical mouth-throat based on data from a CT scan, MRI scan, and living subjects. This idealized model has been the basis of many deposition studies, including deposition in aerosol drug delivery devices (14,56,57). A recent study showed that aerosol deposition in the idealized replica is in close agreement with those in the LRRI realistic mouth-throat replica for liquid aerosol and solid aerosol when the idealized replica is coated to prevent particle bounce (58).…”
Section: Deposition In the Oropharyngeal Regionsmentioning
confidence: 60%
See 1 more Smart Citation
“…This model is an average geometrical mouth-throat based on data from a CT scan, MRI scan, and living subjects. This idealized model has been the basis of many deposition studies, including deposition in aerosol drug delivery devices (14,56,57). A recent study showed that aerosol deposition in the idealized replica is in close agreement with those in the LRRI realistic mouth-throat replica for liquid aerosol and solid aerosol when the idealized replica is coated to prevent particle bounce (58).…”
Section: Deposition In the Oropharyngeal Regionsmentioning
confidence: 60%
“…CFD simulation of the flow pattern using the same oral cavity geometry and aerosol inlets of 3, 5, and 8 μm clearly showed an air jet from the inlet impinging on the back of the mouth (Fig. 8) (56). Deposition efficiency does not correlate with the impaction diameter, d ae 2 Q, which does not include the inlet diameter.…”
Section: Oral Deposition For the Dpismentioning
confidence: 98%
“…Corrections for anisotropy of turbulence at boundary layers were also not employed. Some studies showed that the anisotropy of turbulence at boundary layers can greatly affect the calculation of particle deposition (such as Matida et al (2003) in respiratory track flows and Wang and James (1999) in channel flows). In a study conducted in a ventilated room, Zhao et al (2004) employed a discrete phase boundary layer treatment similar to the current study to simulate particle depositions.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…The relevant governing transport equations are solved in 3D models of the airways, which are discretized into interconnected small spatial elements (or control volumes) such as hexahedral, tetrahedral, or prism cells. Recent CFD studies of inhaled pharmaceutical aerosols have captured the effects of inhalers on transport and deposition in the mouth-throat region (34)(35)(36) and have predicted aerosol deposition through numerous generations of the upper (37)(38)(39) and lower TB airways. (40) However, prediction of aerosol transport and deposition throughout the lungs with CFD simulations (i.e., a CFD whole-lung model) remains challenging and requires simplifying techniques, which are actively being developed.…”
Section: Introductionmentioning
confidence: 99%